What is the Optimal Duration of Middle-Cerebral Artery Occlusion Consistently Resulting in Isolated Cortical Selective Neuronal Loss in the Spontaneously Hypertensive Rat? - Ejaz, Sohail; Williamson, David J.; Jensen-Kondering, Ulf; Ahmed, Tahir; Sawiak, Steve J.; Baron, Jean-Claude (Frontiers in Neurology, 2015)
Introduction and Objectives: Selective neuronal loss (SNL) in the reperfused penumbra may impact clinical recovery and is thus important to investigate. Brief proximal middle cerebral artery occlusion (MCAo) results in predominantly striatal SNL, yet cortical damage is more relevant given its behavioral implications and that thrombolytic therapy mainly rescues the cortex. Distal temporary MCAo (tMCAo) does target the cortex, but the optimal occlusion duration that results in isolated SNL has not been determined. In the present study we assessed different distal tMCAo durations looking for consistently pure SNL. Methods: Microclip distal tMCAo (md-tMCAo) was performed in 6-month old male spontaneously hypertensive rats (SHRs). We previously reported that 45min md-tMCAo in SHRs results in pan-necrosis in the majority of subjects. Accordingly, three shorter MCAo durations were investigated here in decremental succession, namely 30, 22 and 15mins (n=3, 3 and 7 subjects, respectively). Recanalization was confirmed by MR angiography just prior to brain collection at 28 days and T2-weighted MRI was obtained for characterization of ischemic lesions. NeuN, OX42 and GFAP immunohistochemistry appraised changes in neurons, microglia and astrocytes, respectively. Ischemic lesions were categorized into three main types: 1) pan-necrosis; 2) partial infarction; and 3) SNL. Results: Pan-necrosis or partial infarction was present in all 30min and 22min subjects, but not in the 15min group (p < 0.001), in which isolated cortical SNL was consistently present. MRI revealed characteristic hyperintense abnormalities in all rats with pan-necrosis or partial infarction, but no change in any 15min subject. Conclusions: We found that 15min distal MCAo consistently resulted in pure cortical SNL, whereas durations equal or longer than 22min consistently resulted in infarcts. This model may be of use to study the pathophysiology of cortical SNL and its prevention by appropriate interventions.